UTILIZATION OF HOUSEHOLD ORGANIC WASTES FOR COMPOSTING IN SUBURB TAMALANREA JAYA CITY OF MAKASSAR1 - Ifayanti Ridwan (Lembaga Pengabdian pada Masyarakat, 2014)
City waste management is facing a challenge related to limiting spaces for waste disposal in the location of Final Waste Disposal (FWD). Land filling of organic waste in the FWD can be reduced by empowering households to manage organic waste such as food residues. One alternative for household organic waste management is to use it as raw material for composting. The purpose of this community service activities are 1) to increase public knowledge in waste management, 2) provide knowledge to the community about how to compost from organic waste and 3) increasing the availability of compost and composter in the neighborhood residential community. The method used in this program of science and technology for the society was workshop with a participatory learning includes sorting of household waste into organic and inorganic waste categories and Takakura composting method. In addition an evaluation of the program in the target communities was carried out. Participants of the training consisted of 20 units of community household representatives residing in the suburb of Tamalanrea Jaya, district Tamalanrea, Makassar city. From the activity, it can be concluded that there is a large potential in the utilization of organic waste from the household waste based on the simplicity of techniques and materials that easily be available at any time. Some factors to consider in making compost is the condition of the raw material and the process of composting.